2021
DOI: 10.1016/j.mcpro.2021.100173
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ubiquitylome Analysis Reveals the Specificity of RNF111/Arkadia E3 Ubiquitin Ligase for its Degradative Substrates SKI and SKIL/SnoN in TGF-β Signaling Pathway

Abstract: RNF111/Arkadia is an E3 ubiquitin ligase that activates the transforming growth factor-β (TGF-β) pathway by degrading transcriptional repressors SKIL/SnoN and SKI. Truncations of the RING C-terminal domain of RNF111 that abolish its E3 function and subsequently activate TGF-β signaling are observed in some cancers. In the present study, we sought to perform a comprehensive analysis of RNF111 endogenous substrates upon TGF-β signaling activation using an integrative proteomic approach. In that aim, we carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…UBXN7 stabilizes RNF111 in a RING and UAS dependent-manner UBXN7 and RNF111 are both nuclear proteins [5,23]; it is therefore possible that UBXN7 modulates the E3 ubiquitin ligase activity of RNF111 in the nucleus. We and others have shown previously that RNF111 is an E3 ubiquitin ligase that auto-ubiquitylates [22,33,34]. Here we showed that endogenous protein level of RNF111 detected by western-blot on U2OS cell lysates is increased in the presence of the proteasome inhibitor MG132 (Fig.…”
Section: The Uas Domain Of Ubxn7 Directly Interacts With Rnf111 Ring ...supporting
confidence: 65%
See 3 more Smart Citations
“…UBXN7 stabilizes RNF111 in a RING and UAS dependent-manner UBXN7 and RNF111 are both nuclear proteins [5,23]; it is therefore possible that UBXN7 modulates the E3 ubiquitin ligase activity of RNF111 in the nucleus. We and others have shown previously that RNF111 is an E3 ubiquitin ligase that auto-ubiquitylates [22,33,34]. Here we showed that endogenous protein level of RNF111 detected by western-blot on U2OS cell lysates is increased in the presence of the proteasome inhibitor MG132 (Fig.…”
Section: The Uas Domain Of Ubxn7 Directly Interacts With Rnf111 Ring ...supporting
confidence: 65%
“…Such inactivation can be achieved by mutation of the first cysteine of the RING domain to an alanine (CA) that unfolds the first zinc-finger structure (Fig. 1a), and we have shown previously that this mutation abolishes RNF111 E3 ubiquitin ligase activity, SKIL ubiquitylation, and SMADdependent transcription [19,22]. We then compared the interactome of RNF111-WT and RNF111-CA mutant by performing GFP-Trap affinity purification coupled mass spectrometry on HEK-293 cells individually transfected with GFP-RNF111-WT, GFP-RNF111-CA, and GFP as a negative control (Fig.…”
Section: Ubxn7 Interacts With Rnf111 and Rnf165 Arkadia-like Ring Dom...mentioning
confidence: 99%
See 2 more Smart Citations
“…BRCA1 and SKI/SKIL, positive controls for STUbL-mediated protein degradation via RNF4 and RNF111, respectively, showed increased protein stability after the cell treatment with siRNF4 or siRNF111 (fig. S5) ( 41 , 48 ). In these experiments, CP2c protein levels were not augmented by siRNF4 and/or siRNF111 treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%